A expectativa escolar de estudantes do curso de licenciatura em física no campus Arapiraca - Rocha, Josefa Eleusa da (2011)
This research had the purpose to examine a group of tickets at the Bachelor's Degree in Physics from UFAL Campus Arapiraca, started the second half of 2009, aiming to search for elements that contribute to a better understanding of the professionalization of teachers for teaching Physical Education Basic in the current context but also to understand the problems experienced by teachers of physics in their initial training. Based on the assumption that the beginning of the teaching profession in the area of physics is complex and full of uncertainties. The study was a methodological tool, the literature search, which allowed us access to the works of several authors who have made significant contributions on the subject of teacher training and in this case more specifically the training of physics teachers. Also the technique used was the questionnaire, together with the students investigated and analysis of documents that allowed access to important information for the verification of hypotheses. At first discussed questions about teacher training in Brazil with a focus on the Training of Physics Teachers. The second chapter presents issues concerning the structure of the Degree in Physics at the Campus Arapiraca, discussing historical and structural data, highlighting curriculum, and the final chapter of the discussion was moved to drop out of physics courses. In the third chapter, were reviewed and discussed the data obtained through the questionnaire administered to students in the program, which provided information relating to personal and family issues, history and perspectives of the same school with the course.